Meteorological factors associated with grasshopper outbreak at Vagholi village (Solapur district, Maharashtra) in 1975 - KAZI, S. K. (MAUSAM, 1983)
Influence of weather conditions on an outbreak of a spoladic pest are examined. Temperature and precipitation relationship to the abundance of an insect pest are outlined. The analysis supports the belief that weather effects on insects often act over a short period.